Intravenous ketamine plus midazolam is superior to intranasal midazolam for emergency paediatric procedural sedation. Issue 1 (1st January 2001) - Acworth, J P; Purdie, D; Clark, R C
Abstract : Objectives —This study compared intranasal midazolam (INM) with a combination of intravenous ketamine and intravenous midazolam (IVKM) for sedation of children requiring minor procedures in the emergency department. Method —A single blinded randomised clinical trial was conducted in the emergency department of a major urban paediatric hospital. Subjects requiring sedation for minor procedures were randomised to receive either INM (0.4 mg/kg) or intravenous ketamine (1 mg/kg) plus intravenous midazolam (0.1 mg/kg). Physiological variables and two independent measures of sedation (Sedation Score and Visual Analogue Sedation Scale) were recorded before sedation and at regular intervals during the procedure and recovery period. Times to adequate level of sedation and to discharge were compared. Results —Fifty three patients were enrolled over a 10 month period. Sedation was sufficient to complete the procedures in all children receiving IVKM and in 24 of the 26 receiving INM. Onset of sedation was an average of 5.3 minutes quicker with IVKM than with INM (95%CI 3.2, 7.4 minutes, p<0.001). Children given INM were discharged an average of 19 minutes earlier than those given IVKM (95%CI 4, 33 minutes, p=0.02). Mean Sedation Scores and Visual Analogue Sedation Scale scores for the 30 minutes after drug administration were significantly better in children given IVKM compared with INM (2.4 and 1.8 versus 3.5 and 3.8, respectively). Both doctors and parents were more satisfied with sedation by intravenous ketamine and midazolam. Conclusions —Intravenous ketamine plus midazolam used in an appropriate setting by experienced personnel provides an excellent means of achieving sedation suitable for most non-painful minor procedures for children in the emergency department. This combination is superior to INM in terms of speed of onset and consistency of effect. INM delivered via aerosol spray has a more variable effect but may still be adequate for the completion of many of these procedures.